2023
DOI: 10.1128/spectrum.02352-23
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the cecal microbiota of broilers raised in extensive and intensive production systems

Camila S. Marcolla,
Tingting Ju,
Hannah L. Lantz
et al.

Abstract: Intensive broiler production practices are structured to prevent the introduction and spread of pathogens; however, they can potentially minimize the exposure of broilers to beneficial commensal bacteria. In this study, we used 16S rRNA amplicon sequencing to characterize the cecal microbiota of 35-day-old broilers from 22 independent commercial farms rearing broilers under intensive (IPS) or extensive production systems (EPS). We aimed to determine which bacteria are normal inhabitants of the broiler ceca and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 108 publications
1
1
0
Order By: Relevance
“…Our study found that Firmicutes and Bacteroidetes dominated the gut microbiota of both domestic and wild pigs with different ratios. The higher Bacteroidetes in wild pigs was consistent with previous studies exploring the gut microbiota of healthy wild boars (27), which has also been observed in extensively raised chickens (57) and in humans living in rural areas (58, 59). It has been shown that Bacteroidetes are capable of breaking down various types of complex non-digestible carbohydrates in the host gastrointestinal tract, while Firmicutes are well-suited to the cross-feeding process in the gut (60).…”
Section: Discussionsupporting
confidence: 90%
“…Our study found that Firmicutes and Bacteroidetes dominated the gut microbiota of both domestic and wild pigs with different ratios. The higher Bacteroidetes in wild pigs was consistent with previous studies exploring the gut microbiota of healthy wild boars (27), which has also been observed in extensively raised chickens (57) and in humans living in rural areas (58, 59). It has been shown that Bacteroidetes are capable of breaking down various types of complex non-digestible carbohydrates in the host gastrointestinal tract, while Firmicutes are well-suited to the cross-feeding process in the gut (60).…”
Section: Discussionsupporting
confidence: 90%
“…Unfortunately, the chickens analyzed were often colonized by the Campylobacter genus, the most common zoonotic pathogen of foodborne diseases, which distorts microbial networks and does not allow their microbial networks to be considered "normal". Notably, significantly different microbiomes dominated by Firmicutes and Bacteroidetes (currently Bacillotaand Bacteroidota-dominated) have also been described in broiler chickens under extensive production systems (EPS) or intensive production systems (IPS) [35], which showed low and high phylogenetic diversity, respectively. At the same time, the results of cited and present studies are not identical, since the F1(−) pattern did not include the phylum Pseudomonadota (formerly Proteobacteria), the F1(+) pattern included the ACT component, and there were additional differences from the bacterial taxa found to be at the core of the EPS and IPS microbiomes [11].…”
Section: Discussionmentioning
confidence: 99%